Analisis Kinerja Organisasi Kepolisian Resor Asahan dalam Penanganan Kasus Begal di Kota Kisaran - Rendi Yuda Santosah; Muhammad Imanuddin Kandias Saraan (Journal of Research and Development on Public Policy, 2026)
The persistence of street robbery (begal) in Kisaran City threatens public security and creates material and psychological consequences for the community. This study aimed to analyze the organizational performance of the Asahan Resort Police in handling robbery cases. A descriptive qualitative approach was applied, with data collected through interviews, observation, documentation, and literature review. The data were analyzed using Dwiyanto’s organizational performance framework, comprising productivity, service quality, responsiveness, responsibility, and accountability. The findings show that the performance of the Asahan Resort Police was generally effective. Preventive and repressive measures, including targeted patrols, investigation, case disclosure, and public education, contributed to a decline in robbery cases in 2025. Service delivery, responsiveness to reports, and case-handling procedures were also implemented in accordance with institutional duties and applicable standards. Nevertheless, performance remained constrained by limited personnel, a broad jurisdiction, insufficient witnesses and evidence, and inadequate disclosure of case progress to victims and the public. These findings underline the need to strengthen human and operational resources, optimize risk-based supervision, and provide accessible case-progress information to improve handling effectiveness and reinforce public trust in the police.